Neurobehavioral features in individuals with Kabuki syndrome. Issue 3 (13th March 2018) - Caciolo, Cristina; Alfieri, Paolo; Piccini, Giorgia; Digilio, Maria Cristina; Lepri, Francesca Romana; Tartaglia, Marco; Menghini, Deny; Vicari, Stefano
Abstract: Background: Kabuki syndrome (KS) is a disorder characterized by multiple congenital anomalies affecting development and function of multiple systems. Over the years, researchers have attempted to characterize the neurobehavioral phenotype of KS in cohorts of patients enrolled on the basis of clinical assessment. The availability of molecular testing now allows for recruitment of patients with confirmed KS due to KMT2D and KDM6A . Methods: The aims of the present study were to investigate the neuropsychological and behavioral profiles of individuals with molecularly confirmed diagnosis of KS, and determine the extent of heterogeneity occurring in these profiles between individuals with clinical diagnosis of KS with and without mutations in KMT2D . We also described performance of our cohort in any neuropsychological domain investigated. Results: We documented a marked variation in the neuropsychological profile of subjects with clinical diagnosis of KS, even though a relatively homogeneous impairment in linguistic domains and motor skills was observed. No significant difference occurred between mutation‐positive and mutation‐negative groups. Phonological disorders and oromotor dysfunctions were also found, and adaptive functioning was characterized by low performance in daily living and in motor domain. Conclusion: The present study allowed identification of a distinctive neurobehavioral profile in a cohort of individuals affected by KS with or without molecularly confirmed diagnosis. These findings are expected to help clinicians define more accurately targeted protocols for individualized intervention. Abstract : Kabuki syndrome (KS) is a disorder characterized by multiple congenital anomalies affecting development and function of multiple systems. Over the years, researchers have attempted to characterize the neurobehavioral phenotype of KS in cohorts of patients enrolled on the basis of clinical assessment. The aims of the present study were to investigate the neuropsychological and behavioral profiles of individuals with molecularly confirmed diagnosis of KS, and determine the extent of heterogeneity occurring in these profiles between individuals with clinical diagnosis of KS with and without mutations in KMT2D. We also described performance of our cohort in any neuropsychological domain investigated. We documented a marked variation in the neuropsychological profile of subjects with clinical diagnosis of KS, even though a relatively homogeneous impairment in linguistic domains and motor skills was observed. No significant difference occurred between mutation‐positive and mutation‐negative groups. Phonological disorders and oromotor dysfunctions were also found, and adaptive functioning was characterized by low performance in daily living and in motor domain. The present study allowed identification of a distinctive neurobehavioral profile in a cohort of individuals affected by KS with or without molecularly confirmed diagnosis. These findings are expected to help clinicians define more accurately targeted protocols for individualized intervention.